2001
DOI: 10.1354/vp.38-6-667
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-induced Gastritis in Experimentally Infected Conventional Piglets

Abstract: A conventional nonmutant animal that could be experimentally infected with Helicobacter pylori isolates would be a useful animal model for human H. pylori-associated gastritis. Gnotobiotic and barrier-born pigs are susceptible to H. pylori infection, but attempts to infect conventional pigs with this bacterium have been unsuccessful. In the present study, a litter of eight 20-day-old crossbreed piglets were purchased from a commercial farm. Six of them were orally challenged two to five times at different ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
4
8
0
Order By: Relevance
“…Results of this study indicated that that mononuclear cells (lymphocytes and plasma cells) were predominant cell types of inflammatory infiltrate, whereas polymorphonuclear leukocytes (neutrophils) were not present. Previous study also point to lack of neutrophile in inflammatory infiltrate of experimentally induced H. pylori infection in conventional piglets [22]. This is in accordance to results published by other autors [1,3,15,22], but contrary to chronic active gastritis associated with Helicobacter spp.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Results of this study indicated that that mononuclear cells (lymphocytes and plasma cells) were predominant cell types of inflammatory infiltrate, whereas polymorphonuclear leukocytes (neutrophils) were not present. Previous study also point to lack of neutrophile in inflammatory infiltrate of experimentally induced H. pylori infection in conventional piglets [22]. This is in accordance to results published by other autors [1,3,15,22], but contrary to chronic active gastritis associated with Helicobacter spp.…”
Section: Discussionsupporting
confidence: 90%
“…Previous study also point to lack of neutrophile in inflammatory infiltrate of experimentally induced H. pylori infection in conventional piglets [22]. This is in accordance to results published by other autors [1,3,15,22], but contrary to chronic active gastritis associated with Helicobacter spp. in humans [9].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The activity of Myristica fragrans in reducing H. pylori load and thus effecting healing of the gastritis compared favourably well with the control drug (Ofloxacin) which would have been expected to have better activity being a pure drug. There are several animal models available to help understand the pathogenesis of H. pylori infection, including gnotobiotic piglets, athymic mice and monkeys (Poutahidis et al, 2001;Raghavan et al, 2003;Kodama et al, 2005 In addition, the in vitro experiment revealed a broad antibacterial spectrum of nutmeg extracts including activity against some restricted organisms such as H. pylori. However, it did not demonstrate any antibacterial activity against Escherichia coli and Klebsiella pneumoniae tested in our preliminary study.…”
Section: Discussionmentioning
confidence: 99%